Suppurative BCG lymphadenitis and the importance of microbiology investigations – a case report - Muhamad Damanhur, Fatimahtuz Zahrah; Mahayidin, Hasni; Kandasamy, Thenmalar; Zaini, Adilahtul Bushro; Masri, Siti Norbaya; Nordin, Syafinaz Amin (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2020)
Suppurative BCG lymphadenitis can easily be overlooked, as it mimics other diseases such as tuberculous lymphadenitis. A case of a three-month old female infant who received the BCG vaccination at birth presented with isolated left axillary mass at two months of age. She was initially treated as lymph node abscess but was referred to the hospital due to the increasing size of the swelling. Needle aspiration was done and the microbiology analysis came out positive for acid-fast bacilli. She was planned for syrup isoniazid; however, the management team withheld treatment until they were certain of the identity of the bacteria. The bacteria was confirmed by the molecular method to be Mycobacterium bovis BCG strain. The case report highlights the importance of the microbiology investigations for appropriate management in this case.